The Eternal Question: Biological variations on a Platonic dialogue - von Uexküll, Jakob; von Uexküll, Thure; Vögel, Edgar (Sign Systems Studies, 2004)
The reinterpretation of Nature by biology, which will prevail in spite of all obstacles, has brought our thinking closer to antiquity, giving us the chance to reinvigorate our perused terminology with the help of the resources to be found in the thoughts of the greatest minds of mankind. The way to Plato thus being cleared, I perceived the idea to seek enlightenment on pressing biological questions from the great Sage. As means to this end, I chose to make Socrates continue one of his dialogues, with the adjustment of giving him the knowledge of our contemporary biological problems. Thus some kind of interaction between the Ancients and ourselves is created, to our considerable benefit.